Different dispersion states of MWCNT in aligned conductive electrospun PCL/MWCNT composites. Issue 10 (3rd October 2018) - Molinari, Fabricio; Medrano, Anahí V.; Bacigalupe, Alejandro; Escobar, Mariano M.; Monsalve, Leandro N.
ABSTRACT: This work presents the synthesis and characterization of oriented nanofibers made of polycaprolactone (PCL) and multiwalled carbon nanotubes (MWCNT) obtained by electrospinning. The preparation of MWCNT/PCL solutions and electrospinning conditions were studied in order to maximize electrical conductivity of the composite and fiber alignment. The characterization of MWCNT/PCL solutions and fibers revealed the occurrence of different dispersion states for MWCNTs for different loads, which in turn affected the properties of the electrospun composite, such as its double electrical percolation and the in-fiber orientation of the PCL crystals. As the same dispersion states of MWCNT were present in both PCL/MWCNT dispersions and fibers, the rheology of the former can be correlated to the final properties of the latter.